Are socio-economic disparities in diet quality explained by diet cost?. Issue 6 (10th December 2010) - Monsivais, Pablo; Aggarwal, Anju; Drewnowski, Adam
Abstract : Background: Socio-economic disparities in nutrition are well documented. This study tested the hypothesis that socio-economic differences in nutrient intakes can be accounted for, in part, by diet cost. Methods: A representative sample of 1295 adults in King County (WA) was surveyed in 2008–2009, and usual dietary intakes were assessed based on a food-frequency questionnaire. The monetary value of individual diets was estimated using local retail supermarket prices for 384 foods. Nutrients of concern as identified by the 2005 Dietary Guidelines Advisory Committee were fibre, vitamins A, C and E, calcium, magnesium and potassium. A nutrient density score based on all seven nutrients was another dependent measure. General linear models and linear regressions were used to examine associations among education and income, nutrient density measure and diet cost. Analyses were conducted in 2009–2010. Results: Controlling for energy and other covariates, higher-cost diets were significantly higher in all seven nutrients and in overall nutrient density. Higher education and income were positively and significantly associated with the nutrient density measure, but these effects were greatly attenuated with the inclusion of the cost variable in the model. Conclusions: Socio-economic differences in nutrient intake can be substantially explained by the monetary cost of the diet. The higher cost of more nutritious diets may contribute to socio-economic disparities in health and should be taken into account in the formulation of nutrition and public health policy.